FORMULASI GEL PATI BENGKUANG (Pachyrhizus erosus (L.) Urb.) DENGAN GELLING AGENT METILSELULOSA - Husnul Warnida (Jurnal Ilmiah Manuntung, 2015)
Bengkuang roots (Pachyrhizus erosus (L.) Urb.)  empirically have been used as cosmetics materials, primarily as sun screen and whitening agent. Bengkuang roots posses 6 compound which have tyrosinase inhibitory activities. Commercially, bengkuang roots available as whitening cream and lotion but those dosage forms are not suitable for oily skin. In this study the gel was formulated with varying methylcellulose (4% and 5%) as gelling agent. The evaluation included stability, organoleptic, pH, homogeneity, and spreading test. Formula A (4% methylcellulose) meets all physical requirements of gel. The result of acceptability (hedonic test. showed the most acceptance formula was formula A (4% methylcellulose).